Future therapy for non‐alcoholic fatty liver disease. (10th February 2018) - Issa, Danny; Patel, Vaishali; Sanyal, Arun J.
Abstract: Non‐alcoholic fatty liver disease is a leading cause of chronic liver disease and can lead to cirrhosis, hepatocellular cancer and end stage liver disease. It is also associated with increased cardiovascular and cancer related morbidity and mortality. The pathogenesis of non‐alcoholic fatty liver disease includes metabolic stress to the liver associated with insulin resistance with downstream cell stress from reactive oxygen species and unfolded protein response with activation of inflammatory and fibrotic pathways. There are currently no approved therapies for non‐alcoholic fatty liver disease. This review summarizes ongoing efforts to establish the treatment of non‐alcoholic steatohepatitis the progressive form of non‐alcoholic fatty liver disease. Therapies are currently directed towards improving the metabolic status of the liver, cell stress, apoptosis, inflammation or fibrosis. Several agents are now in pivotal trials and it is expected that the first therapies will be approved in 2‐3 years.